Analisis Pengungkapan Global Reporting Initiative Standard (GRI Standard) pada Laporan Keberlanjutan Perusahaan yang Bergerak pada Sektor Pertambangan yang Terdaftar pada Asia Sustainability Reporting Rating (Asrrat) Tahun 2024 - Syahna Shinta Yunari; I. B. Ketut Bayangkara (Universitas Veteran Bangun Nusantara, 2025)
Sustainability reports are very important because they show that a company is not only focused on increasing company profits but also shows the company's commitment to the environment. The purpose of this study is to analyze the reporting of mining companies' social responsibility through the disclosure of GRI Standards in the sustainability report for the period 2022-2023. This study uses a purposive sampling technique in data collection by obtaining a sample of 3 companies. The data analysis technique used in this study is to give points to each GRI standard disclosed.